The prevalence and clinical features of pulmonary embolism in patients with AE-COPD: A meta-analysis and systematic review. - Xiaofang Fu (Public Library of Science (PLoS), 2021)
Background The prevalence of pulmonary embolism (PE) in the acute exacerbation of chronic obstructive pulmonary disease (AE-COPD) is highly controversial. We conducted a systematic review and meta-analysis to summarize the epidemiology and characteristics of PE with AE-COPD for current studies. Methods We searched the PubMed, EMBASE, Cochrane Library and Web of Science databases for studies published prior to October 21, 2020. Pooled proportions with 95% confidence intervals (95% CIs) were calculated using a random effects model. Odds ratios (ORs) and mean differences (MDs) with 95% confidence intervals were used as effect measures for dichotomous and continuous variables, respectively. Results A total of 17 studies involving 3170 patients were included. The prevalence of PE and deep vein thrombosis (DVT) in AE-COPD patients was 17.2% (95% CI: 13.4%-21.3%) and 7.1% (95% CI: 3.7%-11.4%%), respectively. Dyspnea (OR = 6.77, 95% CI: 1.97-23.22), pleuritic chest pain (OR = 3.25, 95% CI: 2.06-5.12), lower limb asymmetry or edema (OR = 2.46, 95% CI:1.51-4.00), higher heart rates (MD = 20.51, 95% CI: 4.95-36.08), longer hospital stays (MD = 3.66, 95% CI: 3.01-4.31) were associated with the PE in the AE-COPD patients. Levels of D-dimer (MD = 1.51, 95% CI: 0.80-2.23), WBC counts (MD = 1.42, 95% CI: 0.14-2.70) were significantly higher and levels of PaO2 was lower (MD = -17.20, 95% CI: -33.94- -0.45, P<0.05) in the AE-COPD with PE group. The AE-COPD with PE group had increased risk of fatal outcome than the AE-COPD group (OR = 2.23, 95% CI: 1.43-3.50). Conclusions The prevalence of PE during AE-COPD varies considerably among the studies. AE-COPD patients with PE experienced an increased risk of death, especially among the ICU patients. Understanding the potential risk factors for PE may help clinicians identify AE-COPD patients at increased risk of PE. Prospero registration number CRD42021226568.